Range-edge genetic diversity: locally poor extant southern patches maintain a regionally diverse hotspot in the seagrass Zostera marina - Diekmann, O. E. (2014)
Refugial populations at the rear edge are predicted to contain higher genetic diversity than those resulting from expansion, such as in post-glacial recolonizations. However, peripheral populations are also predicted to have decreased diversity compared to the centre of a species’ distribution. We aim to test these predictions by comparing genetic diversity in populations at the limits of distribution of the seagrass Zostera marina, with populations in the species’ previously described central diversity ‘hotspot’. Zostera marina populations show decreased allelic richness, heterozygosity and genotypic richness in both the ‘rear’ edge and the ‘leading’ edge compared to the diversity ‘hotspot’ in the North Sea ⁄ Baltic region. However, when populations are pooled, genetic diversity at the southern range is as high as in the North Sea ⁄ Baltic region while the ‘leading edge’ remains low in genetic diversity. The decreased genetic diversity in these southern Iberian populations compared to more central populations is possibly the effect of drift because of small effective population size, as a result of reduced habitat, low sexual reproduction and low gene flow. However, when considering the whole southern edge of distribution rather than per population, diversity is as high as in the central ‘hotspot’ in the North Sea ⁄ Baltic region. We conclude that diversity patterns assessed per population can mask the real regional richness that is typical of rear edge populations, which have played a key role in the species biogeographical history and as marginal diversity hotspots have very high conservation value.